Pengaruh Lokasi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Cateringna.id Bandung - Komalasari, Anisah; Rahayu, Muji (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
The aim of this research is to determine the relationship between Cateringna.id Bandung customer satisfaction and service quality and location. The data collection technique uses a questionnaire. Saturated sampling is the sampling method currently used. This shows that the entire population is included in the sample. Multiple linear regression analysis is the method used for data analysis. The results of the hypothesis test show that customer satisfaction is positively and significantly influenced by the location of Cateringna.id Bandung and the quality of its service. Customer satisfaction is also influenced by these two variables. In other words, improving the quality of places and services will make visitors happier.